2011
DOI: 10.1103/physrevlett.106.075002
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Energetic Ions on Tearing Modes

Abstract: In contrast with the stability effects of trapped energetic ions on tearing modes, the effects of circulating energetic ions (CEI) on tearing modes depend on the toroidal circulating direction, and are closely related to the momentum of energetic ions. CEI provide an additional source or sink of momentum to affect tearing modes. For co-CEI, tearing modes can be stabilized if the momentum of energetic ions is large enough. On the other hand, the growth of tearing modes can be enhanced by counter-CEI. Further, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
99
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(103 citation statements)
references
References 18 publications
(42 reference statements)
4
99
0
Order By: Relevance
“…17) to investigate numerically the interaction between energetic particles and tearing modes. Our simulation results confirmed the analytic results of Cai et al 16 in the limit of small energetic particle beta. New results of circulating energetic particle effects on tearing modes at higher beta as well as trapped energetic particle effects will be shown.…”
Section: Introductionsupporting
confidence: 94%
See 4 more Smart Citations
“…17) to investigate numerically the interaction between energetic particles and tearing modes. Our simulation results confirmed the analytic results of Cai et al 16 in the limit of small energetic particle beta. New results of circulating energetic particle effects on tearing modes at higher beta as well as trapped energetic particle effects will be shown.…”
Section: Introductionsupporting
confidence: 94%
“…16, where it was shown that the effects of energetic ions on tearing modes mainly come from the ideal region of tearing modes due to large drift orbit width of energetic ions. It is known that classical tearing modes are driven by parallel current density gradient with their stability characterized by the parameter D 0 .…”
Section: Physics Picturementioning
confidence: 99%
See 3 more Smart Citations